Consensus treatment recommendations from the tenth International Workshop for Waldenström Macroglobulinaemia. Issue 11 (November 2020) - Castillo, Jorge J; Advani, Ranjana H; Branagan, Andrew R; Buske, Christian; Dimopoulos, Meletios A; D'Sa, Shirley; Kersten, Marie José; Leblond, Veronique; Minnema, Monique C; Owen, Roger G; Palomba, M Lia; Talaulikar, Dipti; et al.
Summary: Waldenström macroglobulinaemia is an indolent B-cell lymphoma with clearly defined criteria for diagnosis, initiation of therapy, and response, which was established by consensus panels at previous International Workshops for Waldenström Macroglobulinaemia (IWWM). The treatment options for Waldenström macroglobulinaemia continued to be researched after the publication of the eighth IWWM consensus recommendations in 2016, and at the tenth IWWM in New York, USA (October, 2018) an international consensus panel was formed to update treatment recommendations. Participants were selected as members of the consensus panel based on their expertise on Waldenström macroglobulinaemia. The initial live discussion took place during the tenth IWWM meeting and two separate teleconferences were held in June, 2019, and January, 2020, to refine recommendations. No external or financial support was received for the elaboration of these recommendations. According to these updated consensus recommendations, alkylating drugs (bendamustine, cyclophosphamide) and proteasome inhibitors (bortezomib, carfilzomib, ixazomib), both in combination with rituximab, as well as BTK inhibitors (ibrutinib), alone or in combination with rituximab, are preferred first-line therapy options for symptomatic patients with Waldenström macroglobulinaemia. In previously treated patients with Waldenström macroglobulinaemia who had an initial durable response, reuse of a previous regimen or another primary therapy regimen are acceptable options. Novel BTK inhibitors (acalabrutinib, zanubrutinib, tirabrutinib) and the BCL2 antagonist venetoclax appear safe and active, and represent emerging options for the treatment of Waldenström macroglobulinaemia. The choice of therapy should be guided by the patient's clinical profile, genomic features, and drug availability.